2016
DOI: 10.1111/spc3.12269
|View full text |Cite
|
Sign up to set email alerts
|

When and Why Mimicry is Facilitated and Attenuated

Abstract: Although people tend to mimic others automatically, mimicry is facilitated or attenuated depending on the specific context. In the current paper, the authors discuss when mimicry is facilitated and attenuated depending on characteristics of situations, targets, and observers. On the basis of the review, the authors propose a new modelthe Associated Reactions to Actions in Context model (ARAC)to explain why and when mimicry is facilitated and attenuated. ARAC proposes that when people observe an action, reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…However, in contrast to automatic imitation, mimicry research has focused more on overlap of opinions or social groups than on overlap of physical characteristics (e.g., Castelli, Pavan, Ferrari, & Kashima, 2009; Yabar, Johnston, Miles, & Peace, 2006). Rather than feature overlap (Press, 2011), this research has argued that similar others are mimicked more often because individuals use mimicry to foster social relations and are more motivated to affiliate with persons that are more like themselves (Lakin & Chartrand, 2003; Stel et al, 2016; Wang & Hamilton, 2012). Interestingly, the idea that affiliation goals shape who we do and who we do not imitate has now also received support from studies on automatic imitation (e.g., J.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to automatic imitation, mimicry research has focused more on overlap of opinions or social groups than on overlap of physical characteristics (e.g., Castelli, Pavan, Ferrari, & Kashima, 2009; Yabar, Johnston, Miles, & Peace, 2006). Rather than feature overlap (Press, 2011), this research has argued that similar others are mimicked more often because individuals use mimicry to foster social relations and are more motivated to affiliate with persons that are more like themselves (Lakin & Chartrand, 2003; Stel et al, 2016; Wang & Hamilton, 2012). Interestingly, the idea that affiliation goals shape who we do and who we do not imitate has now also received support from studies on automatic imitation (e.g., J.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is thought to rely on the same mechanisms as motor mimicry (Heyes, 2011). Moreover, these mechanism are believed to facilitate social interaction (Stel, van Dijk, & van Baaren, 2016; Wang & Hamilton, 2012) and to predict both empathy (Butler, Ward, & Ramsey, 2015; Genschow et al, 2017) and autism spectrum disorder (Spengler, Bird, & Brass, 2010; Williams, 2008; Williams, Whiten, Suddendorf, & Perrett, 2001). Furthermore, automatic imitation is widely considered an index of mirror neuron activation (Bien, Roebroeck, Goebel, & Sack, 2009; Catmur, Walsh, & Heyes, 2009; R.…”
mentioning
confidence: 99%
“…The same point can also be made for the broader literature on social modulation of automatic imitation. Indeed, although it has often been theorized (e.g., Stel et al, 2016; Wang & Hamilton, 2012), evidence for social modulation so far has been inconsistent (e.g., Carr et al, 2021; Cracco & Brass, 2019; Cracco et al, 2022; Cracco, Genschow, et al, 2018; Farmer et al, 2016; Genschow et al, 2022; Nevejans & Cracco, 2022; Ramsey, 2018; Souter et al, 2021; Wang et al, 2011). Based on our results, a possible reason for this pattern could be that the manipulations used in the literature differ in the extent to which they influence self-other similarity and that these differences explain part of the variability.…”
Section: Discussionmentioning
confidence: 99%
“…Research in NT children and adults has shown that both mimicking and being mimicked are strongly linked with increased interaction quality, social bonding between the interactants, and pro-social behaviours (Duffy & Chartrand, 2015;Stel, van Dijk, & van Baaren, 2016).…”
Section: Mimicry Behaviour and Autismmentioning
confidence: 99%